Promoting Safe and Effective Transitions to College for Youth with Mental Health Conditions A Case-Based Guide to Best Practices (Springer International Publishing, 2018)
This concise and practical book provides an overview of how to safely and effectively transition adolescents with mental health conditions into a college environment. Therapeutic strategies to assess and promote readiness for transition to college are discussed in case-based chapters, which include case history, analysis of transition, clinical pearls, literature review, and helpful resources for clinicians, patients, and families. Filling a significant gap in the literature, this resource delivers essential information for psychiatrists, psychologists, and other mental health professionals who work with children, adolescents, and their families before, during, and after the transition to college.